Validity of self-reported fertility-threatening cancer treatments in female young adult cancer survivors - ROBERTS, Samantha C. (J Cancer Surviv, 2017)
PURPOSE: Detailed cancer treatment information is important to fertility and pregnancy care of female young adult cancer survivors. Accuracy of self-report of treatments that impact fertility and pregnancy is unknown. This study assessed agreement between self-report and medical records on receipt of fertility-threatening treatments. METHODS: A national cohort study of female young adult cancer survivors reported cancer treatments via web-based questionnaires. Primary cancer treatment records were abstracted. Self-reported exposure to fertility-threatening therapies (alkylating chemotherapy, stem cell transplant, pelvic radiation, hysterectomy and/or oophorectomy) was compared to medical records. Logistic regression models estimated odds ratios (OR) for characteristics associated with inaccurate self-report of fertility-threatening therapies. RESULTS: The study included 101 survivors (mean age 28.2, SD 6.3). Lymphoma (33%), breast cancer (26%) and gynecologic cancers (10%) were the most common cancers. Accuracy of self-report was 68% for alkylating chemotherapy and 92–97% for radiation, surgery and transplant. Significant proportions of survivors who were treated with transplant (8/13, 62%), alkylating chemotherapy (18/43, 42%), pelvic radiation (4/13, 31%), or hysterectomy and/or oophorectomy (3/13, 23%) did not report undergoing these therapies. In adjusted analysis, age ≤ 25 at diagnosis (OR 3.4, 95% CI 1.3–8.7) and recurrence (OR 6.0, 95% CI 1.5–24.4) were related to inaccurate self-report. CONCLUSIONS: Female young adult cancer survivors have limited recall of fertility-threatening cancer treatment exposures. Reproductive health providers and researchers who need this information may require primary medical records or treatment summaries. IMPLICATIONS FOR CANCER SURVIVORS: Additional patient education regarding treatment-related reproductive risks is needed to facilitate patient engagement in survivorship.